Endoscopic Endonasal Intraconal Approach for Orbital Tumor Resection: Case Series and Systematic Review - Zhang, Xin; Hua, Wei; Quan, Kai; Yu, Guo; Du, Zunguo; Yang, Zixiao; Wang, Xiaowen; Song, Jianping; Chen, Liang; Zhu, Wei (Frontiers in Oncology, 2022)
Intraorbital tumor could be approached by numerous surgical methods. Neuroendoscopic endonasal approach could provide a feasible corridor for indicated tumors. Herein we present a series of 6 consecutive intraorbital tumors from April 2018 to October 2020, which received endonasal endoscopic resection. Cadaveric dissection was performed for the intraconal approach, and the literature was also reviewed. Five tumors were located intraconally, while one extraconally. The pathology revealed 1 angioleiomyoma, 1 cavernous hemangioma, 1 pilocytic astrocytoma, 1 meningioma and 2 schwannomas. Five of the six achieved gross total resection, including 3 tumors with lateral extension beyond the optic nerve. Pre-operative visual deterioration was observed in 4 of the 6 patients, and all got improvement post-operatively. Transient oculomotor nerve palsy was presented in one patient post-operatively. No cerebrospinal fluid leakage, enophthalmos or strabismus was observed. The median follow-up time is 27 months (11~41 months). At 6-month follow-up, the visual acuity remained unchanged compared with that at discharge. Proptosis was resolved in 2 of the 3 patients, diplopia was improved in one patient. In conclusion, endoscopic endonasal intraconal approach could be suitable for selected pathological conditions, and for both medial or beyond medial extraconal and intraconal orbital tumors.